Vine spacing of Vitis vinifera cv. Shiraz/101-14 Mgt. I. root growth and physiological activity - JJ Hunter; CG Volschenk (OENO One, 2024)
Knowledge of vine reaction to plant spacing under relatively high potential soil conditions is limited. This study comprised effects of vine spacing (with fixed row spacing) of Shiraz (clone SH 9C)/101-14 Mgt on a high potential soil in the Breede River Valley, Robertson, South Africa, on soil conditions, root system distribution, and vine physiological reaction. The vineyard was planted in 2008 to a VSP trellis, with a fixed row spacing of 2.2 m and a row orientation of approximately NNE–SSW (30°). In-row vine spacing changed from 0.3–4.5 m with increments of 30 cm (from 15151–1010 vines/ha), totalling 15 treatments. After the completion of cordon development, results were generated over six seasons. Soil conditions seemed generally uniform and showed no obvious characteristics that could have affected treatments differentially. An increase in density occurred in fine, extension and permanent root categories with closer spacing, increasing the total number of roots/ha. Roots penetrated deeper with closer vine spacing. Vine spacing impacted physiological parameters and revealed a complex interplay between root distribution, vine structure expansion, canopy microclimate, water relations, photosynthetic output, berry temperature, carbon distribution, and day/night recovery that would affect grape composition and wine quality. Optimum vine spacing appeared to be 1.8 m, both closer and wider spacing leading to limitations in physiological activity. Interactions amongst below- and aboveground growth and physiological parameters are comprehensively discussed with a focus on sustainability.